2016
DOI: 10.1093/nar/gkw352
|View full text |Cite
|
Sign up to set email alerts
|

DNA compaction by the bacteriophage protein Cox studied on the single DNA molecule level using nanofluidic channels

Abstract: The Cox protein from bacteriophage P2 forms oligomeric filaments and it has been proposed that DNA can be wound up around these filaments, similar to how histones condense DNA. We here use fluorescence microscopy to study single DNA–Cox complexes in nanofluidic channels and compare how the Cox homologs from phages P2 and WΦ affect DNA. By measuring the extension of nanoconfined DNA in absence and presence of Cox we show that the protein compacts DNA and that the binding is highly cooperative, in agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…At lower concentrations of 1:100 PrgB:DNA (DNA concentration in base pairs), we detect both fully and partly compacted DNA molecules in the same sample. This large heterogeneity indicates that the binding of PrgB to DNA is cooperative, and compares well with previous studies on the DNA binding protein Cox from bacteriophage P2 in nanochannels (Frykholm et al ., ). At even lower PrgB concentrations (1:1000 PrgB:bpDNA) we observe both partly compacted and non‐compacted DNA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…At lower concentrations of 1:100 PrgB:DNA (DNA concentration in base pairs), we detect both fully and partly compacted DNA molecules in the same sample. This large heterogeneity indicates that the binding of PrgB to DNA is cooperative, and compares well with previous studies on the DNA binding protein Cox from bacteriophage P2 in nanochannels (Frykholm et al ., ). At even lower PrgB concentrations (1:1000 PrgB:bpDNA) we observe both partly compacted and non‐compacted DNA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Because the lipid bilayer exhibited high capability to avoid nonspecific adsorption of proteins (Figure b,c), it enabled the rapid movement of protein–DNA complexes in the nanochannels (Figure d). Therefore, the lipid bilayer‐based coating is very useful to facilitate the direct visualization of the structure and the dynamics of protein–DNA complexes in nanochannels . Last but not the least, it is worthy of attention that more recently Kitamori and co‐workers demonstrated that the use of a nanochannel coated with a lipid bilayer allowed sampling of a single cell content, which has been a challenge in single cell analysis because of the ultrasmall volume.…”
Section: Nanofluidics With Functionalized Surfacesmentioning
confidence: 99%
“…Where examined, RDFs have been shown to cause large bends in attachment site (att) DNA (λ Xis (Thompson and Landy, 1988) (Cho, Gumport and Gardner, 2002), P2 Cox (Ahlgren-Berg et al, 2009), L5 Xis (Lewis and Hatfull, 2003), P4 Vis (Calì et al, 2004), W Cox (Ahlgren-Berg et al, 2009), P22 Xis (Mattis, Gumport and Gardner, 2008) and Pukovnik Xis (Singh et al, 2014)). The crystal structure of the archetypal RDF, Xis from λ, showed three Xis monomers bound to the X1-X1.5-X2 sites in attR causing a 72° non-planar bend in the DNA, leading to the hypothesis that a twisted microfilament forms (Abbani et al, 2007), a hypothesis supported by DNA compaction studies on P2 Cox (Frykholm et al, 2016). Another apparent common feature of RDFs is relaxed DNA specificity, with binding at noncanonical DNA sites seen in vitro at higher RDF concentrations.…”
Section: Introductionmentioning
confidence: 99%